Nonparametric Analysis of Treatment-Response Tables by Bipredictive Configurai Frequency Analysis - Lienert, G. A.; Netter, Petra (Methods of Information in Medicine, 1987)
Bipredictive configurai frequency analysis (CFA) is introduced as a complement to predictive CFA as a method for analyzing r X c contingency tables with r treatment modalities and c response patterns. It is illustrated by an example from dose effect regression evaluation in a randomized block design.
Keywords: Configurai Frequency Analysis; Nicotine; Dose Response Relationship; Sex Differences